Physics Argumentation-Based Computer-Supported Collaborative Hybrid Learning to Increase Concept Mastery and Argumentation Skills - E. Murdani; A. Suhandi; M. Muslim; A. Setiawan; A. Samsudin; B. Costu (Jurnal Pendidikan IPA Indonesia, 2023)
This study aims to increase the level of concept mastery and argumentation of senior high school students in Singkawang City, West Kalimantan Province, Indonesia. The Physics Argumentation-Based Computer-Supported Collaborative Hybrid Learning (PABCSCHL) model in Socio-Scientific Issues (SSI) especially on the topic of the forest fire on the peatlands has been developed with good validation categories by three pedagogical validators and three assessment validators and been implemented to 200 students. Their argumentation skill levels are measured based on Toulmin Argumentation Pattern. The syntax of the PABCSCHL model is Reading (online), Concept Building, Discussing and Debating (offline), Experiment Designing (online), and Experiment Doing (offline). The core of this model is student collaboration in arguing, debating, and experimenting. From this research, most student solution to anticipate the fire forest on peatlands is burning and waiting until the fire is extinguished perfectly (70 students), monitoring periodically that the fire is completely extinguished (60 students), and limiting the burned area by digging trenches around the site (50 students). Student solutions describe students’ understanding of solving problems posed in group discussion sessions and debates and prove their arguments with experimental data. Before implementing the model, no student has the highest level of argumentation and concept mastery. After that, 23 students have the highest level of concept mastery, and 25 students have the highest level of argumentation. The PABCSCHL model can increase the level of concept mastery and argumentation skills. This model is a new alternative hybrid learning in the post COVID-19 pandemic. Many more SSI can be learning topics to be implemented in this model.